Salidroside targeted cytosolic phospholipase A2 and regulated arachidonic acid metabolomics to attenuate atherosclerosis progression - Qing Liao; Yihua Wang; Rong Huang; Ailu Deng; Han Xu; Wen Guo; Dan Wen; Tianqin Xia; Jiaojiao Bian; Zhengmin Xu; Chunyang Zhou (All Life)
Lipid metabolism disturbances are linked to the development of atherosclerosis (AS), with arachidonic acid (AA) and other downstream metabolites being involved. Cytosolic phospholipase A2 (cPLA2) is a key restriction enzyme in AA metabolism. Salidroside (SAL) reportedly alleviates AS by inhibiting inflammation and slowing cholesterol accumulation; however, its pharmacological action on lipid metabolism remains unclear. We investigated the effects of SAL on AA metabolism and its interaction with cPLA2 in in vivo and in vitro AS models. SAL inhibited lipid accumulation and atherosclerotic plaque formation, reduced M1 macrophage enrichment in the aortic arch, and decreased cPLA2 expression in both models. Interestingly, the prediction and molecular dynamics (MD) analysis of small molecules indicated that SAL may bind to the cPLA2 protein with high affinity, enhancing its stability and flexibility, and inhibiting its activity. The AA metabolome was disordered in PBS-treated AS mice; with 27 metabolites being significantly different from those in SAL-treated mice, including 15-HETE produced by 15-Lox-2. Moreover, knockdown of 15-Lox-2 in macrophages increased lipid accumulation and cPLA2 expression, which were inhibited by SAL. In summary, SAL affects AS by regulating the disordered metabolism of AA in AS, directly binding to cPLA2, and modulating the function of downstream enzymes of AA.